Human Resource Management Practices impacting on Turnover Intention: Evidence from IT Employees in Bangladesh - Kamruzzaman, Md; Rauf, Md Abdur; Shamim, Dr Md Mahfuzul Islam (Research Parks Publishers, 2022)
Organisations' most valuable resource is their human resources, and keeping excellent workers on board is essential for those looking to gain a competitive edge. Organisations use a variety of human resource management (HRM) strategies to control employee churn. The term